WAYS TO IMPROVE SMALL BUSINESS FINANCING SYSTEM BASED ON FACTOR SERVICES OF COMMERCIAL BANKS (Marketing Journal, 2025)
The article examines the role of commercial banks in financing small businesses through factoring services. Based on international experience, digital technology integration, and innovative approaches, the advantages of factoring are analyzed. The study ap plies content and comparative analysis to identify the effectiveness of factoring 109 in enhancing financial stability. The results highlight the need to strengthen cooperation between banks and small businesses, improve the legal framework, and develop services through digital platforms. The proposed measures can accelerate the factoring marketʼs growth, support small business development, and boost economic activity.
Keywords: factoring; commercial banks; small business; financing; digital technologies; international experience